Socioeconomic status, comorbidity and mortality in patients with type 2 diabetes mellitus in Scotland 2004–2011: a cohort study. Issue 6 (17th December 2015) - Walker, Jeremy; Halbesma, Nynke; Lone, Nazir; McAllister, David; Weir, Christopher J; Wild, Sarah H
Abstract : Background: Mortality in people with and without diabetes often exhibits marked social patterning, risk of death being greater in deprived groups. This may reflect deprivation-related differences in comorbid disease (conditions additional to diabetes itself). This study sought to determine whether the social patterning of mortality in a population with type 2 diabetes mellitus (T2DM) is explained by differential comorbidity. Methods: Hospital records for 70 197 men and 56 451 women diagnosed with T2DM at 25 years of age and above in Scotland during the period 2004–2011 were used to construct comorbidity histories. Sex-specific logistic models were fitted to predict mortality at 1 year after diagnosis with T2DM, predicted initially by age and socioeconomic status (SES) then extended to incorporate in turn 5 representations of comorbidity (including the Charlson Index). The capacity of comorbidity to explain social mortality gradients was assessed by observing the change in regression coefficients for SES following the addition of comorbidity. Results: After adjustment for age and Charlson Index, the OR for the contrast between the least deprived and most deprived quintiles of SES for men was 0.79 (95% CI 0.67 to 0.94). For women, the OR was 0.81 (0.67 to 0.97). Similar results were obtained for the 4 other comorbidity measures used. Conclusions: The social patterning of mortality in people with T2DM is not fully explained by differing levels of comorbid disease additional to T2DM itself. Other dimensions of deprivation are implicated in the elevated death rates observed in deprived groups of people with T2DM.